Cancer, a disease of aging (part 1) – trends in older adult cancer mortality in Switzerland 1991–2008 (Swiss Medical Weekly, 2012)
PRINCIPLES: It is crucial for aging societies to evaluate trends in cancer mortality rates of older adults. This study examined socio-demographic and regional characteristics specifically focused on the cancer mortality experience of older adults in Switzerland. METHODS: This study included all individuals ≥65 years based on 1990/2000 censuses linked to mortality records to end of 2008 in the Swiss National Cohort. Gender-age-specific (